Murine hepatic proteome adaptation to high-fat diets with different contents of saturated fatty acids and linoleic acid : α-linolenic acid polyunsaturated fatty acid ratios - Liput Kamila P.; Lepczyński Adam; Poławska Ewa; Ogłuszka Magdalena; Starzyński Rafał; Urbański Paweł; Nawrocka Agata; Jończy Aneta; Pierzchała Dorota; Pareek Chandra S.; Gołyński Marcin; Woźniakowski Grzegorz; et al. (Journal of Veterinary Research)
Some health disorders, such as obesity and type 2 diabetes, are associated with a poor diet and low quality of the fat in it. The type and duration of the diet have an impact on the liver. This investigation uses the proteomic approach to identify changes in the mouse liver protein profile in adaptation to high-fat diets with different saturated fatty acid contents and linoleic acid (18:2n-6) to α-linolenic acid (18:3n-3) fatty acid ratios.